Optimization of low‐cost biosurfactant produced by Bacillus subtilis SASCBT01 and their environmental remediation potential. (1st January 2021) - Selvam, K.; Senthilkumar, B.; Selvankumar, T.
Abstract: The present research aims to enhance the biosurfactant (BS) production using agricultural by‐products as a low‐cost substrate with the statistical approach. BS production from Bacillus subtilis SASCBT01 was carried out with four different variables such as pH, incubation time, cassava peel waste (CPW) and palmira sprout (PS). The model expected the highest emulsification activity of 65 ± 1·2% after 96‐h incubation with 3·0 g l −1 of CPW and PS at pH 7·0. The SASCBT01 strain‐based BS was successful at retrieving up to 18% and the highest Pb removal rates were found at 65%. These BS have considered high quality in bioremediation applications.